2010
DOI: 10.1371/journal.pone.0012055
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Caveolin-1 in Repair of DNA Damage through Both Homologous Recombination and Non-Homologous End Joining

Abstract: BackgroundCaveolin-1 (Cav-1), the major component of caveolae, is a 21–24 kDa integral membrane protein that interacts with a number of signaling molecules. By acting as a scaffolding protein, Cav-1 plays crucial roles in the regulation of various physiologic and patho-physiologic processes including oncogenic transformation and tumorigenesis, and tumor invasion and metastasis.Methodology/Principal FindingsIn the present study we sought to explore the role of Cav-1 in response to DNA damage and the mechanism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 53 publications
4
30
0
Order By: Relevance
“…Our results showed that in two BLBC cell lines, when cells were pretreated with CAV-1 siRNA, DNA-PKcs phosphorylation at T2609 and the increase in KU70/80 following irradiation were specifically abolished, accompanied by increased and sustained DNA damage. Moreover, Zhu et al observed decreased levels of phospho-ATM (Ser 1981) and phospho-checkpoint kinase 2 (CHK2) (Thr 68) and fewer BRCA1 foci upon caveolin-1 knockdown [46]. Taken together, both our data and that of others have demonstrated that caveolin-1 knockdown mitigates the ability of cells to repair DNA damage.…”
Section: Discussionsupporting
confidence: 81%
“…Our results showed that in two BLBC cell lines, when cells were pretreated with CAV-1 siRNA, DNA-PKcs phosphorylation at T2609 and the increase in KU70/80 following irradiation were specifically abolished, accompanied by increased and sustained DNA damage. Moreover, Zhu et al observed decreased levels of phospho-ATM (Ser 1981) and phospho-checkpoint kinase 2 (CHK2) (Thr 68) and fewer BRCA1 foci upon caveolin-1 knockdown [46]. Taken together, both our data and that of others have demonstrated that caveolin-1 knockdown mitigates the ability of cells to repair DNA damage.…”
Section: Discussionsupporting
confidence: 81%
“…Recent reports have identified novel roles of BRCA1 in the regulation of caveolin-1 ( CAV-1 ) transcription and the inhibition of cell invasiveness (219), as well as the physical association with plasma membrane proteins ezrin-radixin-moesin, thus controlling cell spreading and motility, which have significant implications for tumor invasion and metastasis (220). Interestingly, the CAV-1 gene is upregulated in cells treated with ionizing radiation and its expression protects cells after exposure through modulating activities of both the HR and NHEJ pathways (221). …”
Section: Role Of Cell Cycle Checkpoint Control and Dna Repair Genes Imentioning
confidence: 99%
“…Cav-1 plays a crucial role in the regulation of various physiological and pathophysiological processes such as oncogenic transformation, tumorigenesis, tumor invasion and metastasis (42). Furthermore, it is a key protein involved in anoikis tumor metastasis (43), as well as a promising biomarker for identifying clinically significant cancer (37).…”
Section: Discussionmentioning
confidence: 99%